Mechanics reveals the role of peristome geometry in prey capture in carnivorous pitcher plants (Nepenthes) - Moulton, DE; Oliveri, H; Goriely, A; Thorogood, C (2023)
Carnivorous pitcher plants (Nepenthes) are a striking example of a natural pitfall trap. The trap’s slippery rim, or peristome, plays a critical role in insect capture via an aquaplaning mechanism that is well documented. Whilst the peristome has received significant research attention, the conspicuous variation in peristome geometry across the genus remains unexplored. We examined the mechanics of prey capture using Nepenthes pitcher plants with divergent peristome geometries. Inspired by living materials, we developed a mathematical model that links the peristomes’ three-dimensional geometries to the physics of prey capture under the laws of Newtonian mechanics. Linking form and function enables us to test hypotheses related to the function of features such as shape and ornamentation, orientation in a gravitational field, and the presence of ‘teeth’, while analysis of the energetic costs and gains of a given geometry provides a means of inferring potential evolutionary pathways. In a separate modeling approach, we show how prey size may correlate with peristome dimensions for optimal capture. Our modeling framework provides a physical platform to understand how divergence in peristome morphology may have evolved in the genus Nepenthes in response to shifts in prey diversity, availability, and size.